Épocas, notas e citações: a prática historiográfica de Francisco Adolfo de Varnhagen na História Geral do Brasil (1854-1857; 1877) - Silva, Jussara Rodrigues da (2013)
This dissertation aims to discuss the historiographical practice of Francisco Adolfo de Varnhagen through the analysis of the changes by the author in his General History of Brazil in two respects: the historical scholarship and establish a timeline for the national history. The comparison between the first two editions of the work are the privileged objects of analysis, because in this way it is possible to reconstruct the conflicts in the relationship between the author's experience and expectation of their peers in IHGB about the challenges of writing a story modernized in Brazil . Thus, this paper discusses some changes promoted by Varnhagen to republish his work thinking this reissue as a rewriting of history, driven by a change in experience, whether collective or individual, requiring the author somehow taking new methodological approaches also changing their own way of writing history.